Submaximal Responses in Calcium-triggered Exocytosis Are Explained by Differences in the Calcium Sensitivity of Individual Secretory Vesicles - Blank, Paul S. (The Rockefeller University Press, 1998)
A graded response to calcium is the defining feature of calcium-regulated exocytosis. That is, there exist calcium concentrations that elicit submaximal exocytotic responses in which only a fraction of the available population of secretory vesicles fuse. The role of calcium-dependent inactivation in defining the calcium sensitivity of sea urchin egg secretory vesicle exocytosis in vitro was examined. The cessation of fusion in the continued presence of calcium was not due to calcium-dependent inactivation. Rather, the calcium sensitivity of individual vesicles within a population of exocytotic vesicles is heterogeneous. Any specific calcium concentration above threshold triggered subpopulations of vesicles to fuse and the size of the subpopulations was dependent upon the magnitude of the calcium stimulus. The existence of multiple, stable subpopulations of vesicles is consistent with a fusion process that requires the action of an even greater number of calcium ions than the numbers suggested by models based on the assumption of a homogeneous vesicle population.